The Effects of Strength and Conditioning in Physical Education on Athletic Motor Skill Competencies and Psychological Attributes of Secondary School Children: A Pilot Study - Ben J. Pullen; Jon L. Oliver; Rhodri S. Lloyd; Camilla J. Knight (MDPI AG, 2020)
Leading global physical activity guidelines advocate that young children need to engage in activities that strengthen musculoskeletal tissues and improve movement skill competency. The purpose of this study was to examine the effects of delivering strength and conditioning as part of the physical education curriculum on athletic motor skill competencies (AMSC), physical performance, and psychosocial factors. Forty-six school children aged 11-14 were included in the study, and sub-divided firstly by sex and then into intervention and control groups. Intervention groups received nine lessons of strength and conditioning based activities over a six-week period, while the control groups continued with traditional physical education curricula. The resistance training skills battery (RTSB) and tuck jump assessment (TJA) assessed AMSC. Standing long jump distance assessed lower limb strength, and online surveys examined motivation, physical self-efficacy and self-esteem. Male and female intervention groups significantly improved RTSB (p > 0.05) whereas no changes were observed in the control groups. No changes were observed in the intervention groups TJA and only trivial and small non-significant changes in standing long jump performance. Significant increases in motivation of the male intervention group occurred. Strength and conditioning integrated in physical education can improve AMSC in short-term interventions.